Pelatihan Merancang RPP berbasis TPACK dalam Konteks HOTS - Ristati Ristati; Iwan Fauzi; Maria Arina Luardini; Lesly Martha Cecylia Meka; Yoskapela Yoskapela (J-ABDIPAMAS (Jurnal Pengabdian Kepada Masyarakat), 2021)
ABSTRACTIn this technological era, teachers are required to be ready to face the challenges and opportunities of an increasingly complex life in the 21st century and universities as teacher-producing institutions have a moral obligation to provide guidance to teachers so that they are ready to face the challenges that exist in the field of education. The purpose of this Community Service activity is to provide training to SMP Nusantara Palangka Raya teachers on how to develop TPACK-based lesson plans in the context of HOTS. This training needs to be carried out because of the problems experienced by the teachers, including the lack of understanding of TPACK, HOTS, and how to design TPACK-based lesson plans in the context of HOTS. This service activity includes training and practice. The data collection method used is documentation technique by collecting all data and analyzing related documents. The results of the analysis of lesson plans designed by teachers in groups after attending the training show that teachers have been able to integrate TPACK into the lesson plans and implement HOTS (C4, C5, and C6) into the components of the lesson plans. Keywords: Technological Pedagogical Content Knowledge (TPACK), HOTS (Higher Order Thinking Skills) ABSTRAKPada era teknologi ini, guru dituntut untuk siap menghadapi tantangan dan peluang kehidupan yang semakin kompleks di abad 21 dan Perguruan Tinggi sebagai lembaga penghasil guru memiliki kewajiban moril untuk melakukan pembinaan kepada para guru agar dapat siap menghadapi tantangan yang ada dalam bidang pendidikan. Tujuan kegiatan Pengabdian Kepada Masyarakat ini adalah memberikan pelatihan kepada para guru SMP Nusantara Palangka Raya tentang cara menyusun RPP berbasis TPACK dalam konteks HOTS. Pelatihan ini perlu dilakukan karena adanya permasalahan yang dialami guru-guru, antara lain kurangnya pemahaman tentang TPACK, HOTS, dan cara merancang RPP berbasis TPACK dalam konteks HOTS. Kegiatan pengabdian ini meliputi pelatihan dan praktik. Metode pengambilan data yang digunakan adalah teknik dokumentasi dengan cara menghimpun seluruh data dan menganalisis dokumen terkait. Hasil analisis RPP yang dirancang guru secara berkelompok setelah mengikuti pelatihan menunjukkan bahwa guru-guru telah mampu mengintegrasikan TPACK ke dalam RPP serta mengimplementasikan HOTS (C4, C5, dan C6) ke dalam komponen-komponen RPP. Kata Kunci: Technological Pedagogical Content Knowledge (TPACK), HOTS (Higher Order Thinking Skills)